Accountability of Military Members as Perpetrators of Corruption in Defense Equipment Procurement - Rahayu, Dewi; Wicaksana Prakasa, Satria Unggul (Academos, 2022)
Corruption courts are the only judiciary that takes sides in examining, adjudicating, and deciding corruption cases in Indonesia. However, in fact, in handling cases of corruption crimes committed by members of the military, those who have the right to prosecute are military officials and those who can carry out investigations are prosecutors in the military environment. Therefore, this study aims to find out how the role of the Military Court in handling corruption cases in the defense equipment procurement sector. The legal question posed is ; 1.) What is the Criminal Liability of Military Members Who Commit Corruption In The Procurement of Defense Equipment?, and 2.) What are the legal mechanisms that can be carried out in the enforcement of corruption in the procurement of defense equipment? This research uses socio-legal methods. The results of this study argue that 1.) Legal liability for members of the military who commit criminal acts remains in the race against Law No. 31 of 1997 as amended by Law No. 20 of 2001. 2.) There needs to be transparency from defense equipment procurement data so that it can facilitate monitoring or supervision related to goods and services.